Karyotypic studies in wild species of arachis (leguminosae) belonging to sections erectoides, procumbentes and rhizomatosae - Ortíz, Alejandra Marcela (2013)
Fil: Ortíz, Alejandra Marcela. Universidad Nacional del Nordeste. Facultad de Ciencias Exactas y Naturales y Agrimensura; Argentina.